Desain RPS Mata Kuliah Perancangan Sistem Kerja& Ergonomi Berbasis Nilai-Nilai Dasar CHAMPION - Heri Setiawan (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2018)
This study aims to obtain concrete examplesdesign of Semester Learning Plans (RPS) Work System Design & Ergonomics (PSKE) courses based on CHAMPION core values include; Charity, Humanity, Altruism, Managing-capacity, Persistence, Integrity, Open-minded, and Noveltyfrom Industrial Engineering Study Program, Musi Charitas Catholic University with the KKNI program. The basis of harmonization and internalization of the core values of CHAMPION in RPS will give a distinctive characteristic to other universities. Harmonization of RPS is very possible to produce a working system design of the teaching and learning process that is reviewed systemically, holistically, interdisciplinary and participatory so that it has an impact on effective, comfortable, safety, healthy and efficient (ENASE) so that productivity can be optimized. Based on the results of the RPS design study PSKE course, learning outcomes include; the impact attitudes and values of 29.58%, general skills of 14.79%, special skills of 33.80%, and mastery of knowledge of 21.83%. Three interesting learning methods are obtained, namely; student-centered learning is 39.47%, interaction/group discussion is 32.89%, and project-based is 27.63%. Interesting learning experiences, namely; assignments by 29%, compilation of papers by 27%, practice by 20%, surveys or visits by 16%, and comparative studies of 8%. Selected assessment criteria/rubrics, namely; assignment test as learning, project, portfolio of 35.9%, written test of 30.9%, performance test of 16.9%, observation test of 7%, and participation test of 2.8%.